Hambatan dan Kebutuhan Layanan Kesehatan bagi Lansia di Masa Kini - Aini Nadilla; Nabilla Putri; Ria Novia; Utin Anindya Cahyadewi (Jurnal Siti Rufaidah, 2026)
The increasing elderly population in Indonesia necessitates the development of more comprehensive health services, yet various obstacles continue to hinder the fulfillment of these needs. This study aims to identify the main barriers experienced by older adults in accessing contemporary healthcare services and to outline the essential health service needs relevant to this age group. A literature study method was employed by analyzing scientific publications related to elderly health across physical, social, economic, and healthcare system dimensions. The findings indicate that older adults encounter limitations such as reduced mobility, low health literacy, insufficient elderly-friendly facilities, high healthcare costs, and a shortage of healthcare professionals trained in geriatrics. Meanwhile, their primary health service needs include continuous promotive and preventive care, easily accessible healthcare facilities, family support in managing health routines, and user-friendly health technologies. These results highlight the importance of developing more inclusive, affordable, and sustainable health services to improve the quality of life of the elderly in Indonesia.